Mobility, migration and new media: manoeuvring through physical, digital and liminal spaces - Lim, Sun Sun; Bork-Hüffer, Tabea; Yeoh, Brenda S. A. (New media & society, 2016)
This special section assembles perspectives on mobilities, migration and new media that emphasise mobile subjects’ multifarious involvements in overlapping digital spheres, which relate them socially and emotionally to both their home and destination countries. In this introduction, we identify two key themes that connect articles in this collection. First, authors accentuate migration and new media appropriation as a process involving liminal spaces characterized by transition, experimentation and tentativeness. Second, they analyse the subtle frictions that derive from migrants’ embeddedness in digital and offline social fields, shot through with power asymmetries that may simultaneously imply empowerment on one hand, and surveillance and control on the other. Authors draw on empirical case studies of transnational migration in foregrounding multiple mobilities within, to or from Asia.